Postoperative maintenance levonorgestrel-releasing intrauterine system for symptomatic uterine adenomyoma - Ching-Jung Lin; Teh-Fu Hsu; Yen-Hou Chang; Ben-Shian Huang; Ling-Yu Jiang; Peng-Hui Wang; Yi-Jen Chen (Elsevier, 2018)
Objective: To evaluate whether a maintenance levonorgestrel-releasing intrauterine system is effective for preventing the recurrence of postoperative adenomyosis-related symptoms. Materials and methods: From January 2005 through December 2014, a retrospective study including 133 patients with symptomatic adenomyosis undergoing conservative uterine-sparing surgery followed by gonadotropin-releasing hormone agonist treatment was conducted. We excluded the 18 patients who did not meet the inclusion criteria. The patients of intervention group (n = 54) received a levonorgestrel-releasing intrauterine system (LNG-IUS), which was inserted after surgery. The patients without LNG-IUS insertion were enrolled in the control group (n = 61). The primary outcome was improvement of adenomyosis-related dysmenorrhea, which was evaluated by the visual analog scale (VAS) and by hemoglobin (Hgb) and CA-125 levels. Results: Over a 12-month follow-up, the intervention group exhibited a greater reduction in dysmenorrhea as assessed with a VAS score (mean ± SD: 6.5 ± 2.5 vs 4.1 ± 3.6, p = 0.001) and a greater elevation in the Hgb level (2.1 ± 1.9 vs 1.0 ± 1.7, p = 0.008) than the control group. At the end of the 24-month follow-up period, the intervention group also exhibited a greater reduction in dysmenorrhea as assessed with a VAS score (mean ± SD 6.1 ± 2.7 vs 3.7 ± 3.7, p = 0.002) and a greater elevation in the Hgb level (1.9 ± 2.1 vs 0.7 ± 1.8, p = 0.022) than the control group. The CA-125 level was significantly lower in the intervention group during the postoperative follow up (12th month follow-up, intervention vs control, 24.5 ± 28.8 vs 50.1 ± 44.0, p = 0.005; 24th month follow-up, 28.6 ± 26.2 vs 75.4 ± 68.5, p = 0.002). Conclusion: The maintenance therapy of LNG-IUS is effective and well accepted for long-term therapy after conservative surgery for patients with adenomyosis.